Assessment of The Factors Affecting Management of Gender and Sexual Violence Against Women in Rural Communities: A Case Study of Kyanamira Sub County Kabale District. - Tumuheki, Timothy (Kabale University, 2024)
The study assessed the factors affecting the management of gender and sexual violence against women in rural communities. A case study of Kyanamira sub-county Kabale district. It was guided by the objectives which included; assessing the extent to which bride price practices affect the Management of Sexual and Gender-Based Violence against women in Kabale District, examining the effect of cultural norms on the Management of Sexual and Gender Violence in Kabale District, and to establish the extent to which the composition of LC courts affects the relationship between socio-cultural factors and management of sexual and gender-based violence. The researcher used a descriptive survey, which was cross-sectional because the respondents could give their views freely. Data collection methods used in the study included Questionnaires and Focus group discussions. The researcher employed a content analysis method to analyze the data. The emerging themes and opinions were properly analyzed, and compared with the information that was obtained in the literature review. Data was then manually analyzed using a calculator and presented in chronological and logical order. The study findings showed that there was a significant positive relationship between bride price practices and the Management of SGBV against women. With this, it can be summarized that bride payments in Kabale District often served to limit women's rights within family settings and communities. In addition, the bride price meant women's fear of returning to their natal homes without being able to repay the bride price. It also means that women are restricted from legally reporting their spouses to the authorities and bride price practices were found to cause intimidation and isolation of women. Key numerical findings reveal a significant positive relationship between cultural norms and the Management of Sexual and Gender-Based Violence against Women with the following summarized that violence against women is the cultural norm, Women are culturally regarded as subordinate and subjected to violent beating. Survivors of Sexual Gender Violence are afraid of societal humiliation and rarely supported by their families and communities. Based on the inferential statistics obtained earlier, a significant positive relationship was established between the composition of LC courts and Sexual and Gender-Based Violence against Women. With the following summarized Sexual and Gender violence issues were locally addressed to LC courts whenever domestic resolving of such matters failed while most LC courts discriminated against women than males despite females reporting more of the SGBV cases. In addition, fair SGBV cases hearing discrepancies were common and found to negatively affect more women. Finally, some of SGBV's complaints were delayed and affected by fewer LC Court members who had not been trained to handle cases. The researcher recommends that cases/incidences of Sexual and Gender Violence be handled through engaging clan elders, and local leadership in formulating more local family bride price guidelines upon which such practices should be based. This will ensure equal family justice including rights for both men and women thus drawing stability in such families. The researcher recommends that the technocrats in Kabale District train clan leaders and members of LC Courts on the Management of Sexual and Gender-Based Violence against women. This is because these are highly respected by community members and are easily accessible by survivors of Sexual and Gender-Based Violence.